Macroeconomic Relaxation: Adjustment Processes of Hierarchical Economic Structures - Masanao Aoki; Raymond Hawkins (Economics: The Open-Access, Open-Assessment E-Journal, 2009)
We show how time-dependent macroeconomic response follows from microeconomic dynamics using linear response theory and a time-correlation formalism. This theory provides a straightforward approach to time-dependent macroeconomic model construction that preserves the heterogeneity and complex dynamics of microeconomic agents. We illustrate this approach by examining the relationship between output and demand as mediated by changes in unemployment, or Okun's law. We also demonstrate that time dependence implies overshooting and how this formalism leads to a natural definition of economic friction.
Keywords: A12; C31; D50; E24; J21; 330; Macroeconomic adjustment process; microeconomic dynamics; aggregation; anelastic relaxation; Okun's law; time-correlation formalism; Makroökonomik; Zeitökonomik; Dynamisches Gleichgewicht; Mikroökonomische Fundierung; Wirtschaftliche Anpassung; Okun's Law; Theorie